Hyperbaric Normoxia Improved Glucose Metabolism and Decreased Inflammation in Obese Diabetic Rat - Naoto Fujita; Natsuki Goto; Tomoya Nakamura; Wataru Nino; Taketoshi Ono; Hisao Nishijo; Susumu Urakawa (Journal of Diabetes Research)
Hyperbaric treatment improves hyperglycemia and hyperinsulinemia in type 2 diabetes associated with obesity. However, its mode of action is unknown. The purpose of the present study was to investigate the influences of regular hyperbaric treatment with normal air at 1.3 atmospheres absolute (ATA) on glucose tolerance in type 2 diabetes with obesity. The focus was directed on inflammatory cytokines in the adipose tissue and skeletal muscle. Otsuka Long-Evans Tokushima Fatty (OLETF) rats were used as models of type 2 diabetes with obesity and Long-Evans Tokushima Otsuka (LETO) rats served as healthy controls. The rats were randomly assigned to untreated or hyperbaric treatment groups exposed to 1.3 ATA for 8 h d-1 and 5 d wk-1 for 16 wks. Glucose levels were significantly higher in the diabetic than in the healthy control rats. Nevertheless, glucose levels at 30 and 60 min after glucose administration were significantly lower in the diabetic rats treated with 1.3 ATA than in the untreated diabetic rats. Insulin levels at fasting and 120 min after glucose administration were significantly lower in the diabetic rats treated with 1.3 ATA than in the untreated diabetic rats. Hyperbaric treatment also increased interleukin-10 (IL-10) expression in the skeletal muscle and decreased tumor necrosis factor α (TNFα) expression in adipose tissue. These results suggested that TNFα downregulation and IL-10 upregulation in diabetic rats subjected to hyperbaric treatment participate in the crosstalk between the adipose and skeletal muscle tissues and improve glucose intolerance.